THE URGENCY OF INDEPENDENT SUPERVISORY AUTHORITY TOWARDS INDONESIA’S PERSONAL DATA PROTECTION - Yulia Neta; Agsel Awanisa; Melisa Melisa (Fakultas Hukum Universitas Lampung, 2022)
In the Working Committee Meeting of the Draft Law on Personal Data Protection, there was a proposal to establish an Independent Supervisory Authority in the protection of personal data. With the existence of an independent supervisory authority, it is hoped that it will create impartial and optimal independence in its supervision and enforcement. The purpose of this study is to analyze the urgency of the Independent Supervisory Authority in the protection of personal data and the ideal concept of the Independent Supervisory Authority in the protection of personal data in Indonesia based on comparisons in other countries. This study uses a normative legal research method using a statutory approach, a conceptual approach, and a comparative approach. The results of this study indicate that the existence of an Independent Supervisory Authority in Indonesia in enforcing the protection of personal data is very important given the considerations of independence, adequacy, checks and balances, and socialization. Regarding the concept of establishing an Independent Supervisory Authority, there are two choices that can be made in Indonesia, namely by establishing it specifically as a separate institution, such as Hong Kong and South Korea, or embedding and adding to the authority of existing institutions such as in Singapore and the United States. With consideration of efficiency and effectiveness, in Indonesia this can be done by attaching an Independent Supervisory Authority with other related institutions such as the Information Commission with the obligation to change the existing institutional structure as an adjustment.